APRESIASI MASYARAKAT TERHADAP PERTUNJUKAN SALUANG DANGDUT DI KECAMATAN PAUH KOTA PADANG - Febrimawati Febrimawati; Wimbrayardi Wimbrayardi; Yensharti Yensharti (FBS Universitas Negeri Padang, 2012)
The Purpose of this research is to find out the societies’ appreciation on devotee, lover, and creatif lover levels toward saluang dangdut’s performances in Padang city where is held on Pauh subdistrict. During the research, the writers see the live performances of saluang dangdut at Mr. Syahrial house which is the family appreciation to this performance is good, the neighbour and relative’s appreciation is really good. While, the resul of the research on the guest of Mr. Syahrial on this performance at Pauh subdistrict is very good. Keywords: Appreciation, Performance, Saluang Dangdut.